LEARNING LANGUAGE AND CULTURE WITH INTERNET AND MULTIMEDIA TECHNOLOGIES - CHEREDNICHENKO, Galina; SHAPRAN, Lyudmila; KUNYTSIA, Lyudmila (Trends in education, 2010)
Rapid social, economic and technological development of our society creates new challenges for the system of higher education in Ukraine. It's not sufficient to give a student certain knowledge, which can be put into standards, books, textbooks and etc. It is necessary to develop independent, flexible, critical thinking of students.Examining the system of higher education in such a way, the role of information technologies becomes obvious. New innovative technologies are the most powerful source of cognitive activity of students, development of their creative abilities, interests and skills and other intellectual factors.